ANALISIS FENOMENA BAHASA SEA GAMES 2011 "AYO INDONESIA BISA" - Fauzi, Mohd. (Jurnal Ilmu Budaya, 2012)
Discourse analysis as seen ini slogans is a very interesting phenomenon, because it uses indirect way to convey the meaning. There are many things can be analyzed from the slogans such as as the form, meaning, function, value and ideology. The 26th Sea Games slogan “Ayo Indonesia Bisa” has a sifnificant role in provoking the athletes, committees, audiences and Indonesian people. This research focuses on form, function and meaning, values and ideologies in the slogans, and the influences of the persuasive discourse as it is in the slogan to the people. This research therefore reconstructs the cultural studies through the discourse in relation to social, cultural, antropological, and political construct. This research applies descriptive and discourse analysis. This research indicates that the 26th Sea Games 2011 “Ayo Indonesia Bisa,” contains specific forms, using colors as red and white and the colors of rainbow (flowering and full of hope) and a picture of a strong man’s hand. The slogan has a deep meaning, visible, and constructs the spirit of Indonesian people, with deep ideologies.